Digital Poverty Map Among Coffee Farmers in Pupuan and Wanagiri: A Comparative Regional Study - Komang Ema Marsitadewi; I Wayan Sudemen (TRANSFORMASI: Jurnal Manajemen Pemerintahan, 2025)
This study aimed to examine the level of digital poverty among coffee farmers in two regions with different geographical and socioeconomic characteristics, namely Pupuan as well as Wanagiri. The analysis focused on three main indicators such as access to digital devices, digital skills, and productive use of technology. The results were categorized into varying degrees of digital poverty to give an understanding of the situation of each region. The findings showed that coffee farmers in Pupuan generally fell into the low digital poverty category across all three indicators. The farmers had sufficient devices, operating skills, and a strong motivation to use digital technology for economic activities such as marketing coffee via social media, monitoring market prices, and taking part in online training, respectively. This productive use of technology had contributed to increased income and competitiveness. Farmers in Wanagiri tended to be in the middle range of digital poverty, specifically concerning skills and productive use. As access to devices was relatively good, technology use was mostly limited to basic communication or entertainment. Low motivation, limited knowledge, and a lack of modified training were the main barriers to maximizing the economic benefits of digital technology. These findings signified that reducing the digital divide required interventions by providing devices, infrastructure, and focusing on improving skills, motivation, and localized institutional support. Incorporated efforts were expected to promote inclusive digital transformation for farmers in rural areas.